PENGUKURAN TINGKAT KEPUASAN PENGUNJUNG TERHADAP PANTAI VIO-VIO DAN PANTAI MELAYU DI KOTA BATAM - Anggia Arista; Yan Mahesa Damanik (Universitas Putera Batam, 2019)
Batam is a city located in the Riau archipelago., besides being known as an industrial city, Batam City is also a famous tourist attraction, where one of them is a motorcycle tourism ojek, several beaches frequented by local and national tourists are beaches located in the region barelang namely vio-vio beach and Malay beach. The beauty of nature and the attractiveness of building and beach facilities are needed for the advancement of the beaches in the city of Batam in order to advance and develop coastal tourism. To maintain and maintain the number of beach visitors is needed an effort to maintain the quality of service so that visitor satisfaction can be maintained and improved. The purpose of this study is to determine the level of satisfaction of the end using the servqual method based on five aspects, namely tangible, reliability, responsiveness, assurance, and empathy, and by taking a sample of 130 samples. The results of the study of 130 respondents were for the servqual score, which is the average value of the gab for each dimension. Based on the results of research conducted servqual value of each dimension on the vio-vio beach is tangible (-1,014), reliability (-0,910), responsiveness (-0,969) assurance (-0,967), and empathy, namely (-1,077), while for Malay beach are tangible (-1,005), reliability (0,969), responsiveness (-0,938) assurance (-0,883), and empathy (-0,992), and based on servqual score calculation results of the calculation of gab for the five dimensions> -1 which means satisfied, for IPA analysis on the vio-vio beach that needs to be improved is in quadrant I namely the dimensions of reliability, responsiviness and empathy while on the Malay coast is tangible, responsiviness and empathy